A compact implantable MIMO antenna with high isolation and wide bandwidth. Issue 1 (2nd January 2022) - Yin, Bo; Cong, Junhao; Huang, Wen; Xu, Zhu
ABSTRACT: A compact wideband three-unit implantable multiple-in-multiple-out (MIMO) antenna for biomedical applications is proposed in this paper. By loading a "Y" slots on the radiation patch, and a metallized via between the radiation patch and the ground plane, they are jointly designed to reduce the Q value of the antenna unit and improve its bandwidth. At same time, three "wolf-teeth club " slots with filtering characteristics are introduced into the ground plane to isolate the coupling of ground surface current at feed ports of antenna units, so as to improve the isolation between feed ports. The 10 dB bandwidth of the MIMO antenna unit is 1.21 GHz-1.66 GHz, covering the commonly used Wireless Medical Telemetry Services (WMTS) band (1.427–1.432 GHz). And the isolation between units is more than 29 dB in the whole 450 MHz bandwidth, among which the isolation in WMTS band are more than 31 dB. Compared with other implantable MIMO antennas, this design not only integrates more MIMO antenna units in a small area but also each MIMO unit has broadband characteristics.